Drogodependencia de un joven y su afectación en las relaciones familiares - Alvarado Navarrete, Roxana Griselda (2020)
The present case study is about the analysis of a young drug addict and how his addiction has influenced his relationship with his family and his social environment. Techniques such as semi-structured interview, non-participant observation, participant observation were used to carry out this work. , clinic history; also two psychological tests, the first the alcohol, tobacco and substance use (ASISST) consumption test and the second Hamilton anxiety scale. It is evident that the young person with drug dependence presented F12.10 Cannabis abuse without complications, so an appropriate treatment was applied to improve family relationships and with the environment in general; resulting in satisfactory greater communication and attention from the people around him.